The Joint IOC (of UNESCO) and WMO Collaborative Effort for Met-Ocean Services - Pinardi, Nadia; Stander, Johan; Legler, David M.; O'Brien, Kevin; Boyer, Tim; Cuff, Tom; Bahurel, Pierre; Belbeoch, Mathieu; Belov, Sergey; Brunner, Shelby; Burger, Eugene; Carval, Thierry; et al. (Frontiers in Marine Science, 2019)
The Joint Committee for Oceanography and Marine Meteorology (JCOMM), a joint technical commission of IOC of UNESCO and WMO, has devised a coordination mechanism for the fit-for-purpose delivery of an end-to-end system, from ocean observations to met-ocean operational services. This paper offers a complete overview of the activities carried out by JCOMM and the status of the achievements up to 2017. The JCOMM stakeholders are the WMO Members and the IOC Member States, their research and operational Institutions, which mandated JCOMM to devise an international strategy to advance toward the achievement of the United Nations Sustainable Development Goals. The three activity areas, namely the Observation Program Area-OPA, the Data Management Program Area-DMPA and the Services and Forecasting Services Program Area-SFSPA have established several expert teams to contribute to the international coordination. OPA is organized in observing networks connected with different observing technologies, DMPA organizes the overall near-real time and delayed mode data assembly and delivery methodology and architecture and the SFSPA coordinates the met-ocean services stemming out of observations and data management. The future developments should strengthen the coordination in the three program areas considering the inclusion of new and emergent observing technologies, the interoperability of met-ocean data assembly centers and the establishment of efficient research to operations protocols, as well as better fit-for-purpose customized services for the public and private sectors.